Knowledge, attitude, and practice patterns of Indian ophthalmologists regarding medicolegal issues - Deepanshu Agrawal; Aarti Heda; Sayantan Ghosh; Sonal Kalia; Karan Bhatia; Nilesh Kumar; Koushik Tripathy (Indian Journal of Ophthalmology, 2023)
Purpose: To assess the knowledge, attitude, and practice patterns (KAPP) of Indian ophthalmologists regarding medicolegal issues using an initial survey. Methods: An online form was circulated among Indian ophthalmologists of all ages over social media and email by the Young Ophthalmologists Society of India (YOSI) and its medicolegal working group. Anonymous responses were obtained and analyzed for each question. The questionnaire comprised questions about demographic details, KAPP of medicolegal issues including how to deal with medicolegal issues (if faced), medical indemnity insurance, deviation from the recommended minimum sum assured (Rs. 1 crore for Indian ophthalmologists), and legal service providers. Results: A total of 109 responses were obtained. The majority of the respondents were male (60, 55%). More than 50% of respondents (58, 53.2%) were younger than 35 years. More than one-fourth of the respondents were private practitioners (29, 27%), and the majority were of senior consultant designation (45, 41%). Around 80% of respondents (89, 81.6%) were aware of professional indemnity insurance; however, only 54% (n = 59) bought the insurance cover. A majority of the respondents (38, 64.4%) had an indemnity cover of a maximum of Rs. 50 lacs. Only 20% of respondents were aware of the expert body at the state/national level that deals with medicolegal cases. Thirty percent of respondents recommended the ideal cover amount to be more than Rs. 1 crore. Conclusion: The current survey highlights the dismally low rate of awareness of medicolegal issues among ophthalmologists. Specifically, a majority of Indian ophthalmologists surveyed did not have recommended minimum insured cover for professional indemnity insurance. Larger studies are needed to further explore KAPP of Indian ophthalmologists in various medicolegal issues.